Planning of Alternative Embankment Reinforcement on the Roadway. Case Study: Landslide on the Bypass Road of Lombok International Airport - Mandalika Section Km 10+415 to 10+519 - Panji Ageng Ichtiar; Mohamad Khoiri; Dwa Desa Warnana; Herlambang Zulfikar (Journal of Infrastructure & Facility Asset Management, 2025)
The Lombok International Airport – Mandalika Bypass Road experienced a landslide at KM 10+415 to 10+519 in February 2023 during heavy rainfall. The landslide is estimated to have occurred due to the saturation of the embankment caused by groundwater flow and rainwater infiltration. The proposed reinforcement includes the use of foam mortar with thickness variations of 2m, 4m, and 6m, with or without subdrain. Another proposal involves using Rigid Inclusions in the form of controlled modulus columns (CMC) with column spacing variations of 2ø, 3ø, and 4ø, with or without subdrain. Numerical analysis of the safety factor (SF) and deformation (Uy) was conducted using the Plaxis 2D program, both for the initial condition and after reinforcement. In general, the SF and deformations (Uy) for all reinforcement variations meet the reinforcement criteria, i.e., SF > 1.5 and deformations (Uy) < 2cm. The smallest SF of 1.579 was obtained with 4m thick foam mortar with subdrain. The largest deformations (Uy) of 1.656 was found with 2ø column spacing CMC without subdrain. The most effective Stress Reduction Ratio of 0.13 was achieved with 2ø column spacing CMC without subdrain. The influence of the subdrain is not significant because the landslide surface did not reach the groundwater table.